MEMBANGUN KESADARAN MASYARAKAT DALAM PEMELIHARAAN SANITASI LINGKUNGAN DI DESA BATU BELAH - dessyka febria; Andi Irfan; Indrawati Indrawati; Tasriani Tasriani (Universitas Pahlawan Tuanku Tambusai, 2022)
This article provides an overview of public awareness and efforts to build public awareness in maintaining environmental sanitation. The majority of villagers do not have a landfill, which causes them to often experience environmental-based diseases such as diarrhea. the majority of the people of Batu Belah Village still dispose of household waste without sorting the waste first. Lack of public knowledge about the importance of protecting the environment so that people continue to carry out activities that damage the environment and their own health. Using the Participation Action Research (PAR) approach, this community service provides direct counseling to the community accompanied by discussion and question and answer sessions about efforts to maintain environmental sanitation and hygiene in order to create a clean and healthy environment. This service activity is expected to increase public awareness in managing organic waste into compost, form a waste bank initiated by the village to manage inorganic waste so that it has economic value and in the end can help the economy of the village community, especially Batu Belah Village Keywords: Environmental, Sanitation; community awareness